2013
DOI: 10.1016/j.ijfoodmicro.2013.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Survival of foodborne pathogens on inshell walnuts

Abstract: The survival of Salmonella enterica Enteritidis PT 30 or five-strain cocktails of S. enterica, Escherichia coli O157:H7, and Listeria monocytogenes was evaluated on inshell walnuts during storage. Inshell walnuts were separately inoculated with an aqueous preparation of the pathogens at levels of 10 to 4 log CFU/nut, dried for 24 h, and then stored at either 4 °C or ambient conditions (23-25 °C, 25-35% relative humidity) for 3 weeks to more than 1 year. During the initial 24-h drying period, bacterial levels d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…The influence of temperature began to show around day 30, after which a significant decline was observed for the data at 22°C, while no significant decline was observed at either −24 or 4°C (Figure 10.1). These observed survival kinetics for Salmonella on raw peanuts are in line with other published literature, where survival curves for Salmonella in low water activity foods do not follow log-linear kinetics and show significant asymptotic tails (Uesugi, Danyluk, and Harris, 2006;2010, Blessington, Mitcham, andKimber et al, 2012;Blessington et al, 2013a;Blessington et al, 2013b;Keller et al, 2013;Santillana Farakos, Frank, and Schaffner, 2013). The data presented in Figure 10.1 indicate that the best descrip tion of Salmonella survival under these conditions requires a model that includes a nonlinear inactivation rate and the ability to incorporate tailing.…”
Section: Primary Modelssupporting
confidence: 87%
“…The influence of temperature began to show around day 30, after which a significant decline was observed for the data at 22°C, while no significant decline was observed at either −24 or 4°C (Figure 10.1). These observed survival kinetics for Salmonella on raw peanuts are in line with other published literature, where survival curves for Salmonella in low water activity foods do not follow log-linear kinetics and show significant asymptotic tails (Uesugi, Danyluk, and Harris, 2006;2010, Blessington, Mitcham, andKimber et al, 2012;Blessington et al, 2013a;Blessington et al, 2013b;Keller et al, 2013;Santillana Farakos, Frank, and Schaffner, 2013). The data presented in Figure 10.1 indicate that the best descrip tion of Salmonella survival under these conditions requires a model that includes a nonlinear inactivation rate and the ability to incorporate tailing.…”
Section: Primary Modelssupporting
confidence: 87%
“…Salmonella is capable of survival and growth on moist walnut hulls and in hull slurries. When inoculated onto inshell walnuts or kernels, Salmonella, E. coli O157:H7, and L. monocytogenes survive for several months under cool and ambient conditions (5)(6)(7)15). Nut-specific guidance for Good Manufacturing Practices (16) is available, and the walnut industry has published best practices for both growers and processors (23).…”
Section: Resultsmentioning
confidence: 99%
“…After hulling and before storage, in-shell walnuts are dried at #43uC for 12 to 48 h (to moisture levels of less than 8%) (37). Salmonella, Escherichia coli O157:H7, and Listeria monocytogenes can survive for extended periods on both in-shell walnuts (7,15) and walnut kernels (5,6) under typical storage conditions.…”
mentioning
confidence: 99%
“…Blessington et al . also found that foodborne pathogens could survive not only in walnut kernels but also on in-shell walnut surfaces for a long time during storage 19 , 20 . In China, since there are a few reports about nut-induced disease outbreaks, it is necessary to investigate the existence and distribution of bacterial pathogens on nut shells.…”
Section: Introductionmentioning
confidence: 90%